Effect of Frying And Storage on the Quality and Shelf Life of Fried Sweet Potato (Ipomoea Batatas) Chip - Nguyen Phuoc Minh (Journal of Global Pharma Technology, 2016)
Sweet potato is the seventh most important crop in terms of global production. Sweet potatoes are rich in antioxidants, such as phytophenolics and carotenoids which also provide distinct flesh colours. The high perishability of sweet potato roots during storage remains a major constraint. It is widely cooked by deep frying and consumed in forms of French fries and chips. Consumers are increasingly health conscious and trends are moving toward foods with low oil content. This research has been focused on different parameters of drying for minimum oil absorption and sensory palatability while maintaining the most phytochemical components such as total phenolic, total flavonoid and carotenoid; extending product shelf life during packaging and preservation. Results revealed that frying 2.0 cm of sweet potato chip in soybean oil heating at 150oC in 2 minutes was appropriated. Fried sweet potato chip could be preserved for 12 weeks under vaccum at 4oC. Moisture and oil content, as well as colour and texture are important quality attributes of fried sweet potato products. Frying of sweet potato bars is carried out to convert the roots to value added products. Frying method brings out unique flavor and texture to the products that improve their overall acceptability.Keywords: Sweet potato chip, Frying, Shelf life, Carotenoid, Flavonoid, Vaccum.